2022
DOI: 10.21037/qims-21-644
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of foramen ovale flap in the fetuses with true and false positive diagnosis of coarctation of the aorta

Abstract: Contributions: (I) Conception and design: HN Xie; (II) Administrative support: JH Shang; (III) Provision of study materials or patients: Q Zheng;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…On the other hand, we have observed that the presence of a redundant foramen ovale was associated with a lower risk of CoA. This parameter is often found in fetuses with cardiac asymmetry and right dominance (mainly after 28 weeks) in which CoA is not confirmed after birth, probably owing to a restriction to the blood flow into the left ventricle because a large part of the left atrial cavity is occupied by the foramen ovale flap 33,34 .…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, we have observed that the presence of a redundant foramen ovale was associated with a lower risk of CoA. This parameter is often found in fetuses with cardiac asymmetry and right dominance (mainly after 28 weeks) in which CoA is not confirmed after birth, probably owing to a restriction to the blood flow into the left ventricle because a large part of the left atrial cavity is occupied by the foramen ovale flap 33,34 .…”
Section: Discussionmentioning
confidence: 93%
“…7-N° 3, 2023, pp. 1291-1312 Journal Scientific MQRInvestigar 1305 de anillo mitral fue <7.3mm, anillo aórtico <5.4mm e istmo aórtico <3mm, por lo cual se concluye que, la evaluación de estos puntos sobre todo durante el trimestre tres de embarazo ayudan a predecir la CoAo, por lo que, se requerirá de análisis clínicos después del pato para confirmar estos resultados; y finalmente un caso similar en donde se estudió cincuenta y siete fetos con sospecha de CoAo fueron sometidos por ECO por Peng R, et al, (49), de los cuales solo el 19,2% tuvieron la patología confirmada posterior a su nacimiento. Con los resultados expuesto por los autores podemos deducir, que los métodos de diagnóstico para predicción y medición de los parámetros cardiacos para detectar la patología deben ser completados unos con otros e investigar clínicamente más a fondo estos procedimientos para lograr una disminución significativa de falsos positivos de CoAo en RN.…”
Section: Discussionunclassified
“…Vena et al [2] found that in fetuses with RFOF without restrictive foramen ovale (RFO), there may be manifestations on fetal echocardiography mimicking aortic stenosis(AS) or coarctation of the aorta (CoA), especially in type III RFOF. Peng et al [3] 's study similarly indicated that the presence of RFOF can increase the false-positive rate of CoA. Additionally, previous case reports [4][5] have also documented that the redundant flap leads to reduced flow through the mitral valve, consequently causing ventricular disproportion, characterized by a diminishment in the size of the left ventricle.…”
mentioning
confidence: 92%